In the Watercolor Tradition : British Works on Paper from the Mellon Bank Collection - Strazdes, Diana (Pittsburgh : The Carnegie Museum of Art, 1990)
Bell, Vanessa ; Bevan, Robert ; Romberg, David ; Shotter Boys, Thomas ; Callow, William ; Callow, William ; Constable, John ; Constable, John ; Cotman, John Sell ; Cox, David ; Cozens, John Robert ; etc.
In the Watercolor Tradition : British Works on Paper from the Mellon Bank Collection, The Carnegie Museum of Art, Pittsburgh, November 3, 1990 - January 6, 1991
boek